In vitro adaptation of Plasmodium falciparum reveal variations in cultivability. (December 2016) - White, John; Mascarenhas, Anjali; Pereira, Ligia; Dash, Rashmi; Walke, Jayashri; Gawas, Pooja; Sharma, Ambika; Manoharan, Suresh; Guler, Jennifer; Maki, Jennifer; Kumar, Ashwani; Mahanta, Jagadish; et al.
Abstract Background Culture-adaptedPlasmodium falciparum parasites can offer deeper understanding of geographic variations in drug resistance, pathogenesis and immune evasion. To help ground population-based calculations and inferences from culture-adapted parasites, the complete range of parasites from a study area must be well represented in any collection. To this end, standardized adaptation methods and determinants of successful in vitro adaption were sought. Methods Venous blood was collected from 33P. falciparum -infected individuals at Goa Medical College and Hospital (Bambolim, Goa, India). Culture variables such as whole blood versus washed blood, heat-inactivated plasma versus Albumax, and different starting haematocrit levels were tested on fresh blood samples from patients. In vitro adaptation was considered successful when two four-fold or greater increases in parasitaemia were observed within, at most, 33 days of attempted culture. Subsequently, parasites from the same patients, which were originally cryopreserved following blood draw, were retested for adaptability for 45 days using identical host red blood cells (RBCs) and culture media. Results At a new endemic area research site, ~65 % of tested patient samples, with varied patient history and clinical presentation, were successfully culture-adapted immediately after blood collection. Cultures set up at 1 % haematocrit and 0.5 % Albumax adapted most rapidly, but no single test condition was uniformly fatal to culture adaptation. Success was not limited by low patient parasitaemia nor by patient age. Some parasites emerged even after significant delays in sample processing and even after initiation of treatment with anti-malarials. When 'day 0' cryopreserved samples were retested in parallel many months later using identical host RBCs and media, speed to adaptation appeared to be an intrinsic property of the parasites collected from individual patients. Conclusions Culture adaptation ofP. falciparum in a field setting is formally shown to be robust. Parasites were found to have intrinsic variations in adaptability to culture conditions, with some lines requiring longer attempt periods for successful adaptation. Quantitative approaches described here can help describe phenotypic diversity of field parasite collections with precision. This is expected to improve population-based extrapolations of findings from field-derived fresh culture-adapted parasites to broader questions of public health importance.